Meningkatkan Pemahaman Siswa Kelas V SDN 1 Cikukulu Tentang Keputusan Bersama Pada Mata Pelajaran PKN Melalui Metode Diskusi - Indriyani, Ikoh (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The background of this research was that Civics Education learning about joint decisions has not achieved satisfactory results and there were still many students who scored below the Minimum Completeness Criteria. Most students had difficulty in understanding the notions of joint decisions and were less active in learning activities so that students had not fully mastered the material of joint decisions. This study aimed to improve students' understanding and learning outcomes about joint decisions by creating a conducive learning situation by applying the discussion method. The subjects of this action research were fifth grade students of State Elementary School of 1 Cikukulu semester II for the 2021/2022 academic year. Research data obtained by means of observation, documentation and field notes. From the analysis of research data, the following conclusions are drawn: 1). The learning planning carried out by the teacher by applying the discussion method can be a guide for the teacher in the implementation of learning so that learning is directed and student activities are guided. 2). The learning process carried out by the teacher by applying the discussion method can increase student activity in participating in learning activities so that students are active in digging up information about learning materials and have implications for increasing students' understanding of learning materials. 3). With the implementation of the discussion method in learning about joint decisions at State Elementary School 1 Cikukulu, it can increase the conduciveness of learning because learning occurs in multiple directions, learning is not focused on the teacher alone, students become active in participating in learning activities.